Bis(imino)-6, 7-dihydro-5H-quinoline-cobalt complexes as highly active catalysts for the formation of vinyl-terminated PE waxes; steps towards inhibiting deactivation pathways through targeted ligand design. Issue 63 (15th December 2021) - Han, Mingyang; Zuo, Zheng; Ma, Yanping; Solan, Gregory A.; Hu, Xinquan; Liang, Tongling; Sun, Wen-Hua
Abstract : Narrowly dispersed PE waxes with high levels of vinyl functionality are produced using the depicted cobalt polymerization catalysts. Abstract : A set of five related bis(imino)-6, 7-dihydro-5 H -quinoline-cobalt(ii ) complexes, [2-(ArN = CPh)-8-(NAr)-C9 H8 N]CoCl2 (Ar = 2, 6-Me2 C6 H3 Co1, 2, 6-Et2 C6 H3 Co2, 2, 6-i-Pr2 C6 H3 Co3, 2, 4, 6-Me3 C6 H2 Co4, 2, 6-Et2 -4-MeC6 H2 Co5 ), have been synthesized in reasonable yield by the template reaction of cobalt(ii ) chloride hexahydrate, 2-benzoyl-6, 7-dihydro-5 H -quinolin-8-one and the corresponding aniline. The molecular structures of Co1 and Co4 highlight both the differences in the two imino-carbon environments (phenyl-capped chain vs. cyclic) and also the steric properties exerted by the bulky N imine -aryl groups. On pre-treatment with either modified methylaluminoxane (MMAO) or methylaluminoxane (MAO), all complexes proved productive catalysts for the polymerization of ethylene. In particular, Co1 /MAO was the most active reaching a very high level of 1.62 × 10 7 g PE per mol (Co) per h over a 30 minute run time. Owing to the presence of the imino-phenyl substituent, Co1–Co5 were able to exhibit good thermal stability by displaying appreciable catalytic activity at temperatures between 50 and 80 °C, generating polyethylenes with narrow dispersities ( M w / M n range: 1.66–3.28). In particular, the least sterically bulky precatalysts, Co1 and Co4 formed polyethylene waxes ( M w range: 1.94–5.69 kg per mol) with high levels of vinyl unsaturation as confirmed by high temperature 1 H/ 13 C NMR spectroscopy and by IR spectroscopy.